Characterizations of damages of DNA caused by plasma treatment and reactive species formed thereby†. (13th May 2015) - Kwon, Young‐Wan; Jin, Jung‐Il; Domb, Abraham; Slomkowski, Stanislaw
<x xml:space="preserve">Abstract</x> Plasma sources at atmospheric pressures have been studied to develop plasma treatment for a variety of biomedical applications. But in such systems, reactive oxygen nitrogen species (RONS) induce severe damage in cells. Here, we briefly introduce atmospheric pressure plasma sources, review recent progress in characterization tools, and present results for RONS in the interface, aqueous system, and cellular components obtained via optical emission spectroscopy, fluorescence indicators, and electron paramagnetic resonance spectroscopy. Gel electrophoresis, circular dichroism spectroscopy, and Raman spectroscopy are used to investigate the damage caused by RONS that reaches the central cellular components and severely modifies DNA. Copyright © 2015 John Wiley & Sons, Ltd.